Optimisation of aetiological examination processes for enhanced quality and efficiency in hospitalised patients prior to antimicrobial therapy: a multicentre quasi-experimental study - Yan Liu; Mei Lin; Xiao Zhong; Li-Hua Xiao; Lan-Fang Mo; Shan-Wen Yang; Lan-Fang He; Qin-Fei Wu; Xiao-Feng Luo (BMJ Open Quality)
Objectives This study aimed to optimise the aetiological examination process in hospitalised patients to enhance pathogen detection quality and efficiency. The hypothesis was that process management strategies would improve specimen submission rates, quality, timeliness and antimicrobial use adjustment.Design A multicentre quasi-experimental pre–post comparison design was used, with baseline and postoptimisation phases.Setting Two hospitals in Guangming District, Shenzhen, China.Participants 34 790 inpatients in the baseline and 34 361 in the postoptimisation phase, across all departments.Interventions Implemented process clarification, standardisation of specimen collection/submission and multidisciplinary collaboration, with comprehensive staff training.Primary and secondary outcome measures The primary outcome measures were the pathogen submission rate before antimicrobial therapy. The secondary outcome measure was the adjustment rate of antimicrobial use based on test results, specimen qualification rate and specimen submission time. These measures were evaluated before and after process optimisation.Results Postoptimisation, key metrics improved significantly: pathogen submission rate (50.82%–71.77%), specimen qualification rate (90.20%–98.71%), submission time (192–104 min) and antimicrobial adjustment rate (74.11%–93.24%; all p<0.001).Conclusions Process management effectively enhanced aetiological examination quality and efficiency, with potential for widespread adoption.Trial registration number Not applicable as this was a quasi-experimental study.